Indicators of socio-economic development - Adamović Jelka M. (Glasnik Srpskog Geografskog Društva, 2002)
Work elaborates indicators witch refers to socio - economic development. In the first part of work it is stated indicators which different authors are used. These indicators are used in empirical researches and in some sources there are theoretically treated. In the second part it is with the aid of induction method performed separation of indicators. It is elaborated economics, social, technological and indicators of urbanization. In the part of economical indicators are elaborated: national income per capita, structure of activities, level of expending.